Fatwa in Indonesia : An Analysis of Dominant Legal Ideas and Mode of Thought of Fatwa-Making Agencies and Their Implications in the Post-New Order Period - Pradana Boy Z. T. F., 1977- (Book collections on Project MUSE., 2018)
This book looks at fatwa in Indonesia during the period following the fall of President Suharto. It is an in-depth exploration of three fatwa-making agencies (Majelis Ulama Indonesia, Lajnah Bahth al-Masail Nahdlatul Ulama, and Majelis Tarjih Muhammadiyah), all of which are highly influential in shaping religious thought and the lives of Muslims in Indonesia. Rather than look at all the fatwa that have emerged in the period, Pradana Boy ZTF focuses on those that have strong repercussions for intra-community relations and the development of Indonesian Muslims more generally, including fatwa pertaining to sectarianism, pluralism, secularism and liberalism.